Interpersonal Communication of Students in the Film Rukuh in Building Religious Moderation - Achmad Tohari (Ittishol: Jurnal Komunikasi dan Dakwah, 2024)
This study aims to analyze the interpersonal communication between characters in the film Rukuh to illustrate the values of religious moderation. The film, which was screened at the 2023 Religious Moderation Short Film Festival, depicts the reality of students in Indonesia and their religious diversity. Using a descriptive qualitative approach and content analysis, this study examines the interactions between characters from different religious backgrounds. This analysis is based on five components of interpersonal communication, namely respect, understanding, empathy, humility, and openness. The findings of this study highlight the importance of interpersonal communication in fostering healthy and effective social relationships, strengthening community networks, and facilitating tolerance in a religious context. This study emphasizes the role of religious moderation in promoting a balanced and fair approach to religious practice characterized by tolerance, compassion, and respect for human dignity. The film Rukuh is an example of how the media can convey positive messages and moral values to its audience, especially in the context of religious moderation among students in Indonesia. This study contributes to the understanding of the importance of interpersonal communication skills in developing self and social skills, as well as increasing mutual understanding in a religiously diverse society.